The Federal Democratic Republic of Ethiopia : Ex-Post Assessment of Long-Term Fund Engagement. (IMF Staff Country Reports; Country Report ;, 2005)
This paper presents an Ex Post Assessment of Long-Term IMF Engagement in Ethiopia. IMF involvement since 1992 helped underpin the authorities' gradualist policies. Initially, IMF-supported programs aimed at stabilizing the economy and breaking with the legacy of central planning. Later programs emphasized structural reform to support sustainable high growth and poverty reduction. Although macroeconomic stability has been largely achieved, structural reform was gradual and piecemeal, especially under the Enhanced Structural Adjustment Facility. Many of the most immediate and distortionary policies of the centrally planned past have also been overhauled.